Soccer game! - Maccarone, Grace; Johnson, Meredith (New York : Cartwheel Books/Scholastic, 1994)
Brief rhyming text follows a group of children through some exciting plays during a soccer game.
BR
BR
Keywords: Soccer -- Fiction; Stories in rhyme